Efeito da temperatura de bobinamento na laminação de tiras a quente sobre as propriedades mecânicas de um aço multifásico da classe de 800 MPa de limite de resistência com requisitos de expansão de furo - Luciano Santos Marques (2019)
Currently, the hot rolling mill at the Ipatinga Steel Plant is able to produce materials of the 900 MPa strength class. However, to meet the hole expansion requirement, this limit is 600 MPa. The present work will evaluate the influence of coiling temperature on hot strip rolling on the microstructure, the tensile strength and hole expansion index of a strength class 800 MPa in hot rolled multi-phase steel. This parameter affects both the size and morphology of the microstructural constituents, as well as the morphology of the formed precipitates, influencing its final mechanical properties. The best results of the coiling temperature for the production of this steel could be determined from the obtained results, taking into account not only the tensile mechanical properties but also the hole expansion capacity specified in standards.